New Trends and Recent Care Approaches in Pediatric Oncology Nursing - Ebru Kilicarslan Toruner; Naime Altay (Elsevier, 2018)
Increased incidence of children diagnosed with cancer and survivors was an impact on changes in pediatric hemato-oncology nursing care. In this review article, it is aimed to investigate the new trends and recent care approaches in pediatric oncology nursing. The recent care topics were common in the literature as family-centered care, technology-based care, program development, primary care of child, health-care provider, survivors and home care, and nonpharmacological care. All of the topics contribute to perform evidence-based care for health promotion and well-being in pediatric hemato-oncology nursing. Research reviews showed that many current topics for the care of children and their parents have entered in the literature. There is a need for more randomized controlled studies to improve the level of evidence of new nursing approaches.